Multiple genotypes of Phelipanche ramosa indicate repeated introduction to the Americas - Schneider, Adam C. (American journal of botany, 2025)
Premise Phelipanche ramosa is an economically damaging parasitic plant that has been reported in North America since the late 1800s. While this species comprises a variety of genetically distinct host races in its native range, the genetic composition of adventive populations in the New World remains unexplored. On the basis of morphological and ecological variation, some have suggested that the closely related P. nana may also be present. Methods Genome skimming was used to assess the relationships of 30 populations of Phelipanche spanning the geographic and host ranges in North and South America, plus one P. nana reference population from Lebanon. Results Phylogenetic analysis indicated four distinct genetic groups, though plastome and nrDNA data supported conflicting signals of relationships among them. First, specimens from Chilean tomato fields were nearly indistinguishable genetically from the reference P. nana. Second, a pair of samples from Virginia showed similar nrDNA as the first group, but divergent plastomes. The remaining 24 samples sorted into two groups, one which parasitizes cultivated plants, especially tomato, and the other on roadside weeds in different parts of the United States. Conclusions The geographic and ecological cohesiveness of four distinct genetic groups supports a hypothesis of multiple introductions to the Americas, presumably from Eurasia, followed by little to no subsequent gene flow among them. However, such groups do not align with existing morphological or ecological species concepts for P. ramosa and P. nana. In practice, threat assessment of Phelipanche populations to agricultural settings should be evaluated regionally given the phylogeographic and ecological heterogeneity.